Hankel Inequalities for a Subclass of Bi-Univalent Functions based on Salagean type q-Difference Operator - Sibel YalÃ§Ä±n; Åžahsene AltÄ±nkaya; Gangadharan Murugusundaramoorthy; Kaliappan Vijaya (Journal of Mathematical and Fundamental Sciences, 2020)
In this investigation a new subclass of bi-univalent functions is established that is defined in the open unit disk Î”={ðŒ¶ âˆˆ â„‚: |ðŒ¶| < 1} and are endowed with the SÄƒlÄƒgean type q-difference operator. Then, Hankel inequalities for the new function class are obtained and several related consequences of the results are also stated.